THE EFFECTIVENESS OF TEACHING READING COMPREHENSION ON DESCRIPTIVE TEXT THROUGH COMIC STRIPS - Awalta, Miza; ., Sudarsono; Arifin, Zainal (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2016)
Abstract: The research was conducted to find out the effectiveness of comic strips to teach English reading comprehension on descriptive texts to Year-7 students of â€œSMPN 22 Pontianakâ€ in Academic Year 2014/2015. The research method was a quasi-experimental research with one group as experimental group and another group as the control group. The subject of the research was class VIIB as experimental group and class VIIC as control group. The research data were collected by a test. Both groups were given pre-test and post-test to measure the studentsâ€™ ability of reading comprehension. The data was analyzed by effect size formula. The obtained effect size was 0.61. It was larger than 0.51 but less than 1.00 and be categorized as moderate. Thus, the effectiveness of comic strip to teach English reading comprehension of descriptive texts to Year-7 students of â€œSMPN 22 Pontianakâ€ in Academic Year 2014/2015 was moderate. Â  Key words: Comic Strips, Teaching Reading Comprehension, Descriptive Texts. Abstrak: Penelitian ini dilakukan untuk mengetahui efektivitas dari komik strip untuk mengajar pemahaman membaca bahasa Inggris pada teks deskriptif untuk siswa kelas tujuh "SMPN 22 Pontianak" di tahun ajaran akademik 2014/2015. Metode penelitian yang digunakan adalah quasi-eksperimental dengan satu kelompok sebagai kelompok eksperimen dan kelompok lain sebagai kelompok kontrol. Subyek penelitian adalah kelas VIIB sebagai kelompok eksperimen dan VIIC kelas sebagai kelompok kontrol. Data penelitian dikumpulkan dengan tes. Kedua kelompok diberi pre-test dan post-test untuk mengukur kemampuan siswa dari membaca pemahaman. Data dianalisis dengan rumus effect size. Effect size yang diperoleh adalah 0.61. Jumlah ini lebih besar dari 0.51 tetapi kurang dari 1.00 dan dikategorikan sebagai moderat atau sedang. Dengan demikian, efektivitas komik strip untuk mengajar pemahaman membaca bahasa Inggris pada teks deskriptif untuk siswa kelas tujuh "SMPN 22 Pontianak" tahun ajaran akademik 2014/2015 adalah moderat atau sedang. Â  Kata Kunci: Komik Strip, Mengajar Pemahaman Membaca, Teks deskriptif.